(untitled) (LACCEI, 2024)
This paper presents an overview of the recent enhancements implemented in guiEditor, a graphical user interface (GUI) editor for GNU Octave. The focus is on the improved functionality and usability of the tool, which is designed to facilitate the development of applications for teaching industrial process control systems. The potential of this tool for solving classroom problems and supporting laboratory experiences for students is demonstrated. The success achieved in the implementation of guiEditor is a evidence to its efficacy and encourages further development of the tool. These promising results motivate future research to explore the potential of guiEditor in facilitating the development of educational tools for industrial process control systems.